2019
DOI: 10.1108/ihr-10-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Happy feelings: examining music in the service environment

Abstract: Purpose The purpose of this paper is to examine the psychological influence that the presence of music has on consumers’ evaluations of the service environment. Specifically, it investigates how emotion regulation processes and the impact of emotions/mood are linked to consumers’ evaluation of service and product quality. Design/methodology/approach An exploratory study was conducted using industry professionals in order to garner insight about the value of music and its benefits in the service environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Exciting music leads to higher emotional arousal in respondents as measured via their skin conductance and heart rate (Zimny & Weidenfeller, 1963). Tourist businesses can use background music to increase emotional arousal and customers' behavioural intentions (Ryu & Jang, 2007) and enhances their experience (Pan, Su, & Chiang, 2008;Jang, Liu, & Namkung, 2011;Kemp, Williams, Min, & Chen, 2019). Music is used in tourism advertisements to influence or change an individual's perceptions of a destination (Pan & Hanusch, 2011).…”
Section: The Effect Of Music On Emotionsmentioning
confidence: 99%
“…Exciting music leads to higher emotional arousal in respondents as measured via their skin conductance and heart rate (Zimny & Weidenfeller, 1963). Tourist businesses can use background music to increase emotional arousal and customers' behavioural intentions (Ryu & Jang, 2007) and enhances their experience (Pan, Su, & Chiang, 2008;Jang, Liu, & Namkung, 2011;Kemp, Williams, Min, & Chen, 2019). Music is used in tourism advertisements to influence or change an individual's perceptions of a destination (Pan & Hanusch, 2011).…”
Section: The Effect Of Music On Emotionsmentioning
confidence: 99%
“…Andersson et al (2012) found a significant effect for time spent in store, where consumers spent more time during the music condition compared to the no music condition. “Music is integral to adding value to the customer experience” (Kemp et al , 2019). As compared to no music condition, Kemp et al (2019) found that music has a significant impact on the mood of the consumers: better perception towards service quality; better perception of product quality; and a higher intention for patronisation.…”
Section: The Influence Of Music As An Atmospheric Stimulusmentioning
confidence: 99%
“…“Music is integral to adding value to the customer experience” (Kemp et al , 2019). As compared to no music condition, Kemp et al (2019) found that music has a significant impact on the mood of the consumers: better perception towards service quality; better perception of product quality; and a higher intention for patronisation.…”
Section: The Influence Of Music As An Atmospheric Stimulusmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that things like Ambiance and Service have more impact on a consumer's willingness to pay than the quality of your food. In the context of background music, if the customer loves the restaurant's environment and background music is also engaging him to enjoy the food, he will pay more even with a handsome tip (Kemp et al, 2019).…”
Section: Customer's Emotions and Spend Moneymentioning
confidence: 99%